Role of parents on screen time of young children in Pokhara metropolitan, Nepal- a cross sectional study - Koirala, Sharad; Banstola, Sanju; Shrestha, Nirmala; Gurung, Nisha; Sah, Saurabh Kishor; Sharma, Bimala (Journal of Gandaki Medical College-Nepal, 2021)
Background: Sedentary lifestyle is a major modifiable risk factor that usually starts from childhood. High screen time is associated with sedentary lifestyle in children; and parents might have played a role in screen time among the children. This study aims to assess the role of parents in the screen time of young children aged five to nine years in Pokhara metropolitan city in Nepal. Methods: A cross sectional study was done among 360 children where respondents were one of the parents of those children. Face to face interview was done using a semi structured questionnaire between March 8 and September 4, 2020. A daily screen time <2 hours was taken as a normal value. Descriptive and inferential analyses were done with the data. Chi square test at 5% level of significance was computed for the inferential analysis. The ethical approval was taken from the Nepal Health Research Council. Results: Of the total 360 children, 54.7% were male and 35.6% were aged 9 years. Screen time >2 hours was found among 48.6% children. The screen time of >2 hours children was significantly associated with the educational qualification of parents, parental worry and parental permission to watch the screen for tasks like eating, doing homework, not going out or making free time for parents. The screen time of children was not associated with socioeconomic characteristics like parental occupation. Conclusion: Parental characteristics have role in the screen time of children. Parental factors must also be considered while implementing programs to reduce children’s screen time.